Governo eletrônico e informação sanitária no Brasil - Raminelli, Francieli Puntel (2015)
The use of technological tools by governments as a way to access the citizen and inform him about matters of public interest is a relatively recent movement and is linked to a culture of transparency, in which the citizen has the power to control the paths taken by their state. This governance model is termed Electronic Government and in Brazil it has been adopted for more than 15 (fifteen) years. The advances in this area have been strengthened with the advent of the Brazilian Information Access Law, Law nº. 12.527/11, which states that access to information is the rule and secrecy to the exception. In this way, all Brazilian government agencies are linked to the provisions of this law that determines the maximum disclosure and transparency in Brazil. Among these, the Ministry of Health draws attention for, in addition to dealing with theme of universal interest, make heavy use of electronic resources on the Internet, and cited here only three: the Portal of Health, the health blog and the Ministry of Page Health on Facebook. So, the question is: the Ministry of Health, in using these online environments, follows the guidelines of the culture of access to information? Moreover, how happens the relationship between him and the Internet citizens who use their official websites? In order to determine what is e-government and how the new information and communication technologies help in the realization of the right to access to information, specifically in the Brazilian Ministry of Health, were used the method of deductive approach, the method of a monographic procedure and techniques of indirect documentation of research (literature and documents) as well systematic intensive direct observation in the environments analyzed on the Internet. It is concluded that despite using up of electronic tools intensively and Law nº 12.527/11 represent an advance in public transparency of the country, Brazil is still far short in other respects, requiring other protection measures for the user to ensure the democratic rule of law which aims to be.